Experiments with a Gas-Puff-On-Wire-Array Load on the GIT-12 Generator for Al K-shell Radiation Production at Microsecond Implosion Times - Shishlov, Alexander V; Baksht, Rina B; Chaikovsky, Stanislav A; Fedunin, Anatoly V; Fursov, Fedor I; Kovalchuk, Boris M; Kokshenev, Vladimir A; Kurmaev, Nikolai E; Labetsky, Aleksey Yu; Oreshkin, Vladimir I; Rousskikh, Alexander G; Lassalle, Francis; et al. (AIP conference proceedings, 2006)
Results of the experiments carried out on the GIT-12 generator at the current level of 3.5 MA and the Z-pinch implosion times from 700 ns to 1.1 mus are presented. A multi-shell (triple-shell) load configuration with the outer gas puffs (neon) and the inner wire array (aluminum) was used in the experiments. In the course of the research, implosion dynamics of the triple-shell z-pinch was studied, and the radiation yield in the spectral range of neon and aluminum K-lines have been measured. Optimization of the inner wire array parameters aimed at obtaining the maximum aluminum K-shell radiation yield has been carried out. As a result of optimization of the gas-puff-on-wire-array Z-pinch load, the aluminum K-shell radiation yield (hv > 1.55 keV) up to 4 kJ/cm in the radiation pulse with FWHM less than 30 ns has been obtained. Comparison of the experimental results with the results of preliminary 1D RMHD simulations allows a conclusion that at least 2/3 of the generator current is switched from a gas puff to an aluminum wire array. The radiation yield in the spectral range of neon K-lines (0.92-1.55 keV) increases considerably in the shots with the inner wire array in comparison with the shots carried out with the outer gas puffs only. The radiation yield in the spectral range above 1 keV registered in the experiments reached 10 kJ/cm. The presence of a high portion of the neon plasma inside an inner wire array can limit the radiation yield in the spectral range above 1.55 keV.